The Mediating Role of Work Motivation on Employee Performance at Property Industry - David Maulany; Denta Ananda (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to determine the influence of leadership, organizational culture, and work competence on employee performance with work motivation as a mediating variable at PT ABC and PT XYZ as two major player in the property industry. The research uses a quantitative approach with purposive sampling and involves 84 permanent non-managerial employees as respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that leadership, organizational culture, and work competence have a positive and significant effect on work motivation. Furthermore, work motivation positively affects employee performance and successfully mediates the relationship between the three variables and employee performance. This study implies that improving work motivation can enhance the influence of internal company factors on achieving optimal employee performance. This work add recommendation to decision maker in the organization in putting alternative strategies to improve employee performance from leadership, organization culture and work competence through the mediation of work motivation. Beside practical side, this article also broaden theoretical implication to human resource management from motivational theory point of view.